Preeclampsia – long-term effects on mother and child - Wieteska, Małgorzata; Maj, Dominik; Gorecka, Adrianna; Zaremba, Bartłomiej (Journal of Education, Health and Sport, 2021)
Preeclampsia (PE) is a pregnancy complication that affects 5% to 8% of all pregnancies. It is a leading cause of maternal mortality that contributes annually more than 60,000 maternal deaths all over the world. Data submitted so far by clinicians are still insufficient to completely understand the disease. Despite many researches, the prediction of patients suffering from PE remains difficult. Moreover therapeutic methods are also limited and concentrated on symptomatic treatment and early termination of pregnancy. The aim of the presented article is to review current research on the PE and its long-term effects on mother and child. PE is defined as a hypertension developing after 20 weeks of gestation with at least one of the following symptoms: proteinuria, maternal organ dysfunction or foetal growth restriction. Because initially patients may be completely asymptomatic, the diagnosis is usually difficult. Untreated PE may lead to the death of both mother and neonate. In later life it predisposes woman and child to cardiovascular and metabolic diseases. Maternal consequences are related to increased risk of hypertension, stroke, thrombosis or chronic kidney disease, whilst offspring implications are directly correlated with hypertension, increased body mass index, hormonal changes and reductions in cognitive functions. In the future there is a need to develop more effective diagnostic methods of PE. Comprehensive understanding of the pathophysiology would allow to avoid many negative long-term effects and reduce its mortality rate.